Awareness and Usage of Electronic Resources among LIS Scholars of Jiwaji University, Gwalior : A Survey - Soni, Navin Kumar; Gupta, Kapil Kumar; Shrivastava, Jitendra (DESIDOC Journal of Library & Information Technology, 2018)
The survey is an attempt to determine and find the present status of awareness, accessibility and use of electronic resources among library and information science research scholars of Jiwaji University Gwalior, like; CD-ROM databases, online databases, online journals, OPAC etc. The study was done to find out the challenges, benefits, and progress gained by research scholars while accessing the e-resources. It is found out through study that ‘Shodhganga’ was mostly used (95 per cent) by research scholars, followed by DOAJ. It was also found out that research scholars got information about available e-resources and databases in their institute through the library website (45.5 per cent), followed by searching on Internet. A detailed result of this survey was discussed and recommendations were made to improve and enhance the usage of e-resources.